(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Oil samples collected from three fishes namely Sting Ray (Dasyatis uarrnak), Anchovy (Setipinna taty), and Eel (Congresox talabonoides) from the Bay of Bengal were analyzed to determine their fatty acid composition with the aid of Gas Liquid Chromatography (GLC). The saturated fatty acid contents were 52.95, 45.28 and 52.29 %; and the unsaturated fatty acid contents were 43.97, 54.72 and 33.39 % in D. uarnak, S. taty and C. talabonoides respectively. The highest polyunsaturated fatty acid content was found in S. taty (13.65 %) and the lowest was in D. uarnak (8.06 %). The ψ-3 fatty acid contents were 4.58, 3.65 and 9.91 % and the ψ-6 fatty acid contents were 3.48, 10.00 and 5.50 % in D. uarnak. S. taty and C. talabonoides respectively. Two essential fatty acid linoleic acid (4.12 %) and arachidonic acid (5.32 %) contents were found higher in S. taty whereas another essential fatty acid linolenic acid (8.98 %) found higher in C. talabonoides. Another important polyunsaturated fatty acid eicosapentaenoic acid (2.12%) found higher in D. uarnak. Bangladesh J. Sci. Ind. Res. 41(1-2), 47-54, 2006